1982
DOI: 10.1136/adc.57.4.268
|View full text |Cite
|
Sign up to set email alerts
|

Protein and fat absorption in prolonged diarrhoea in infancy.

Abstract: SUMMARY 15N-yeast protein absorption, nitrogen and fat retention, stool reducing substances, and lactate concentrations were measured in 22 infants who had had severe diarrhoea for 7 days. Stool losses of nitrogen and fat were large. and an appreciable proportion appeared to be endogenous. The supply of nitrogen and energy might have been a limiting factor in tissue repair if stool weight exceeded 30 g/kg body weight a day. These results differ from those in older children with kwashiorkor complicated by diarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 7 publications
3
9
0
Order By: Relevance
“…Similar results have been previously reported (2,13). Severe diarrhea persisting for 7 days has been shown to be associated with large nitrogen and fat stool losses (14). These losses would limit tissue repair and predispose to the vicious cycle of protracted diarrhea and malnutrition.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results have been previously reported (2,13). Severe diarrhea persisting for 7 days has been shown to be associated with large nitrogen and fat stool losses (14). These losses would limit tissue repair and predispose to the vicious cycle of protracted diarrhea and malnutrition.…”
Section: Discussionsupporting
confidence: 85%
“…Maki et al found high FA-I-AT concentrations in acute childhood diarrhea (8). Mann et al suggested that the low levels of serum albumin found in infants on the 7th day of persistent diarrhea could be interpreted as evidence for significant gastrointestinal loss of plasma proteins (15). Our results confirm that enteric protein loss may complicate post-enteritis syndrome.…”
Section: Discussionsupporting
confidence: 82%
“…Our results confirm that enteric protein loss may complicate post-enteritis syndrome. As a low or negative nitrogen balance has been demonstrated in prolonged diarrhea in children (15), PLE could be an important trigger of the development of the vicious cycle of malnutrition and diarrhea that could delay intestinal repair.…”
Section: Discussionmentioning
confidence: 99%
“…As of yet, no other data on risk factors associated with nutritional therapy using culturally acceptable diets are available. However, earlier studies of nutritional therapy for diarrhea have also indicated that malnutrition, fever, and initial severity of stooling may be linked to poorer outcome (9,(22)(23)(24)(25)(26)(27)(28)(29). If these findings are substantiated by other studies, a clinical assessment profile may be developed which could help guide health care workers to identify children who require more supervised therapy or hospitalization.…”
Section: Discussionmentioning
confidence: 99%